1997
DOI: 10.1111/j.1525-1594.1997.tb00444.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polyethylene Glycol Conjugated Bovine Hemoglobin in Both Top‐Load and Exchange Transfusion Rat Models

Abstract: The purpose of this study was to determine the effect of the hemoglobin based oxygen carrier, polyethylene glycol conjugated bovine hemoglobin (PEG-Hb) on the physiology of the rat. This study was divided into the following 3 parts: pharmacokinetics, cardiovascular, and histopathology. Pharmacokinetic studies evaluated the PEG-Hb circulatory life and the resultant effect on urine composition. Telemetric intravascular blood pressure probes monitored the heart rate and mean arterial pressure. Renal arterial bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…So, it's reasonable that transfusion of PEG-bHb (about 100 kD) led to upregulate lysosome numbers in cytoplasm of liver and kidney as observed. The vacuolar changes were reversible, as proved by Conover et al [16], and confirmed by another research work on dogs in our lab.…”
Section: Discussionsupporting
confidence: 81%
“…So, it's reasonable that transfusion of PEG-bHb (about 100 kD) led to upregulate lysosome numbers in cytoplasm of liver and kidney as observed. The vacuolar changes were reversible, as proved by Conover et al [16], and confirmed by another research work on dogs in our lab.…”
Section: Discussionsupporting
confidence: 81%
“…PEG-Hb™ has been previously reported to be safe and effective in a number of animal species models [59,60,61,62]. Changes in the plasma concentration of PEG-Hb™ after a top-load infusion (25 mL/kg) was examined in rats and rabbits, and the findings showed that the mean half-life was approximately 17 h and 43 h in rats and rabbits, respectively [61,63]. In addition, PEG-Hb™ was shown to have a half-life of 15 h and 58 h in rat and dog models of 30% blood volume exchange transfusion [62,64].…”
Section: Acellular Type Hbocsmentioning
confidence: 99%
“…Furthermore, PEG-Hb™ showed a longer half-life than native Hb in a canine hemorrhagic shock model [65] These long half-lives, as summarized in Table 3, indicate that PEG modification can prevent excretion via glomerular filtration due to the increase in overall molecular weight. In fact, less hemoglobinuria were observed in animals that had been injected with PEG-Hb™ than those injected with native Hb [61,63]. Although PEG-Hb™ had earlier proceeded to Phase Ib, its development for clinical use was stopped more than 20 years ago [3].…”
Section: Acellular Type Hbocsmentioning
confidence: 99%
“…In addition, the various studies investigating this issue have reported some contradictory findings. In the case of bHb, while tests in a rat model showed that PEG-bHb but not unmodified bHb induced formation of vacuoles in the renal proximal convoluted tubules and splenic macrophages [10], another study conducted in a rabbit model showed the opposite result in the hepatocyte cytoplasm [9]. The same agents when tested in dogs all displayed renal tubular vacuole formation [7].…”
Section: Introductionmentioning
confidence: 99%
“…Vacuolation caused by high dosages of PEG-TNFbp was only partially reversible. Interestingly, when PEG was tested alone in two of these studies, it did not show any sign of vacuolation [8,10]. Thus, the currently available information is not sufficient to conclude whether there is indeed a cause-and-effect relationship between PEGylation and vacuolation.…”
Section: Introductionmentioning
confidence: 99%